Beyond instrumental citizenship: the Spanish and Italian citizenship regimes in times of crisis. Issue 14 (26th October 2018) - Finotelli, Claudia; La Barbera, MariaCaterina; Echeverría, Gabriel
ABSTRACT: The aim of this article is to contribute to the current debate on integration during economic downturn by analysing to what extent citizenship regimes may offer opportunities for instrumental uses of naturalisation in times of economic crisis. Its main goal is to provide a more nuanced view of citizenship acquisition, its implications and its alleged instrumental uses to stabilise legal status and improve mobility chances. For this purpose, our analysis focuses on the nexus between citizenship regimes and naturalisations trends in Italy and Spain as two major Southern European immigration countries that have similar migration histories, but rather different citizenship regimes. The first part of the article provides an overview of the scholarly debate on the concept of instrumental citizenship and elaborates a typology of the possible instrumental uses by states and migrants. The second part examines the citizenship regimes and analyses the opportunity structures opened up by citizenship acquisition channels in Italy and Spain. Finally, the article analyses naturalisation trends to show that instrumental uses of citizenship acquisition are closely connected to the different opportunity structures offered by the Italian and Spanish citizenship regimes.